Hanok the Korean house - Park, Nani; Fouser, Robert; Yi, Chong-gŭn, 1969- (Tokyo Tuttle Publishing, 2014)
Twelve examples of the Korean house style, traditional on the exterior and in use of natural materials but with contemporary interiors.
Oidong Pyulchang -- house in Oi-dong -- Yun Posun Residence -- Residence of Yun Posun, second president of Korea -- Mumuheon -- house full of emptiness -- Jamyeongseosil -- Jamyeong's house of playing and reading -- Jiwuheon -- house of continuous learning -- Simsimheon -- house where the heart is found -- Seonyudang -- house of sharing and kindness -- Bansongjae -- studio cherishing an old pine tree as a lifelong friend -- Moto Hanok -- Moto house -- Cheongsongjae and Neungsoheon -- house of a green pine tree and trumpet vine -- Changseongdong Jip -- house in Changseong-dong -- Hwadongjae -- house of becoming one with others -- Acknowledgments -- Designers and architects.
Keywords: Architecture, Domestic -- Korea (South); Architecture, Domestic -- Korea (South) -- Pictorial works; Interior architecture -- Korea; Hanok- Arquitectura tradicional- Korea